Hyperglycemia-induced oxidative stress and epigenetic regulation of ET-1 gene in endothelial cells - Binjawhar, Dalal Nasser; Alhazmi, Alaa T.; Bin Jawhar, Wejdan Nasser; MohammedSaeed, Walaa; Safi, Sher Zaman (Frontiers in Genetics, 2023)
Introduction: Hyperglycemia-induced endothelial dysfunction and the subsequent increase of oxidative stress could lead to aberrant regulation of various genes which are responsible for a range of functions. This study aims to find out how hyperglycemia affect oxidative stress and then the expression and methylation of endothelin 1 (ET-1) gene in in human umbilical vein endothelial cells (HUVEC). Methods: Cells were cultured in growth medium and exposed to low and high glucose concentrations to mimic normal and diabetic condition respectively. Computational analysis were performed using UCSC genome browser and eukaryotic promoter database (EPD). The expression of ET-1 gene was investigated by real time PCR. Cytotoxicity and oxidative stress were determined by MTT and DCFH-DA assays respectively. Promoter methylation was assessed by the bisulfite sequencing method. Results: DCFH-DA assay showed that hyperglycemia can significantly increase the regulation of reactive oxygen species synthesis. The relative expression of ET-1 gene was increased due to exposure to high glucose concentration. MTT assay revealed reduced viability of cells due to the glucose induced damage. Methylation analysis revealed hypomethylation of the promoter of ET-1 however the difference was not significant. Out of 175 CpGs at 25 CpG sites, only 36 CpGs were methylated (20.5% methylation) in cell treated with normal glucose. Upon exposure to high glucose only 30 CpGs were methylated in 175 CpGs at 25 CpG sites (17.1% methylation). Discussion: Our study concludes a significantly high expression of ET-1 gene in response to high glucose exposure in HUVECs. It also reports that hyperglycemic condition leads to elevated oxidative stress. No significant change was found in methylation when cells were treated with high and low glucose concentrations.